ACNAP Congress – perspectives from an established allied professional researcher - Kinga Balla (European Journal of Cardiovascular Nursing, 2026)
Abstract Attending the ACNAP2026 Congress for the first time was a highly valuable and inspiring experience. I particularly appreciated the opportunity to gain insights into different healthcare systems and to learn more about the various roles of healthcare professionals across Europe and other continents. The congress offered a broad scientific programme with poster sessions, workshops and symposia covering various topics in cardiovascular care. I focused on sessions closely related to my clinical and research interests, particularly personalised exercise prescription, cardiovascular rehabilitation and patient engagement. Three aspects were especially relevant to my work. First, the interactive workshop ‘Let the Games Begin: Games for Heart’ by Aseel Berglund [1] provided insights into the potential role of gamification in improving health outcomes among patients with cardiovascular disease. Second, the workshop ‘Precision in Motion: A Practical Workshop on Personalised Exercise Prescription’, led by Stefan Tino Kulnik and Dominique Hansen, offered practical perspectives on individualised exercise prescription. These concepts were further explored during the symposium ‘From Prescription to Performance: Tailoring Exercise and Motivational Skills for Optimal Outcomes’, where Stefan Tino Kulnik [2], Dominique Hansen [3], and Jennifer Jones [4] presented evidence-based approaches to exercise prescription and strategies to support long-term adherence in cardiovascular rehabilitation. Third, I had the opportunity to present my poster entitled ‘Effects of Intensive Early Physiotherapy Intervention after Myocardial Infarction on the Functional Capacity Assessed with the 6-Minute Walk Test’ [5]. Sharing our work with an international audience was a valuable experience and stimulated constructive discussions with experts in the field.